Supramodal Enhancement of Auditory Perceptual and Cognitive Learning by Video Game Playing - Zhang, Yu-Xuan; Tang, Ding-Lan; Moore, David R.; Amitay, Sygal (Frontiers in Psychology, 2017)
Medical rehabilitation involving behavioral training can produce highly successful outcomes, but those successes are obtained at the cost of long periods of often tedious training, reducing compliance. By contrast, arcade-style video games can be entertaining and highly motivating. We examine here the impact of video game play on contiguous perceptual training. We alternated several periods of auditory pure-tone frequency discrimination (FD) with the popular spatial visual-motor game Tetris played in silence. Tetris play alone did not produce any auditory or cognitive benefits. However, when alternated with FD training it enhanced learning of FD and auditory working memory. The learning-enhancing effects of Tetris play cannot be explained simply by the visual-spatial training involved, as the effects were gone when Tetris play was replaced with another visual-spatial task using Tetris-like stimuli but not incorporated into a game environment. The results indicate that game play enhances learning and transfer of the contiguous auditory experiences, pointing to a promising approach for increasing the efficiency and applicability of rehabilitative training.